Lineage specification of parietal epithelial cells requires ß-Catenin [Beta-Catenin]/Wnt signaling - Grouls, Stephan; Wentzensen, Nicolas; Kriz, Wilhelm (Journal of the American Society of Nephrology, 2012)
ß-Catenin/Wnt signaling is essential during early inductive stages of kidney development, but its role during postinductive stages of nephron development and maturation is not well understood. In this study, we used Pax8Cre mice to target ß-catenin deficiency to renal epithelial cells at the late S-shaped body stage and the developing collecting ducts. The conditional ß-catenin knockout mice formed abnormal kidneys and had reduced renal function. The kidneys were hypoplastic with a thin cortex; a superficial layer of tubules was missing. A high proportion of glomeruli had small, underdeveloped capillary tufts. In these glomeruli, well differentiated podocytes replaced parietal epithelial cells in Bowman’s capsule; capillaries toward the outer aspect of these podocytes mimicked the formation of glomerular capillaries. Tracing nephrogenesis in embryonic conditional ß-catenin knockout mice revealed that these “parietal podocytes” derived from precursor cells in the parietal layer of the S-shaped body by direct lineage switch. Taken together, these findings demonstrate that ß-catenin [Beta-Catenin]/Wnt signaling is important during the late stages of nephrogenesis and for the lineage specification of parietal epithelial cells.
Published online January 6, 2012
Gesehen am 14.06.2018